(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
the given article reveals the interaction of English and Uzbek languages through synchronic and diachronic analysis. It shows in which professional fields English words can be present and the important role played by the English language in the development of the Uzbek language in professional relations. Also, the article has shed light on some linguoculturological aspects of these both languages to show the comparisons and contrasts between them using analytical methods of research